2023
DOI: 10.1111/jnc.15833
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase in lipid metabolism: A new outlook

Abstract: Cholinesterase enzymes acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) are traditionally associated with the termination of acetylcholine mediated neural signaling. The fact that these ubiquitous enzymes are also found in tissues not involved in neurotransmission has led to search for alternative functions for these enzymes. Cholinesterases are reported to be involved in many lipid related disease states. Taking into view that lipases and cholinesterases belong to the same enzyme class and by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Some studies have shown reduced ACHE in AD patients, while elevated levels of ACHE variants T30 and T14 have been found [53]. It is worth noting that lipase and cholinesterase belong to the same class of enzymes [54]. There are also numerous reports linking changes in lipid metabolism, live cells, apoptotic cells, and the distribution of necrotic brain cells to the activity of acetylcholinesterase in serum and brain [55].…”
Section: Molecular Dynamics Simulation Of the Ache-6-gingerol Complexmentioning
confidence: 99%
“…Some studies have shown reduced ACHE in AD patients, while elevated levels of ACHE variants T30 and T14 have been found [53]. It is worth noting that lipase and cholinesterase belong to the same class of enzymes [54]. There are also numerous reports linking changes in lipid metabolism, live cells, apoptotic cells, and the distribution of necrotic brain cells to the activity of acetylcholinesterase in serum and brain [55].…”
Section: Molecular Dynamics Simulation Of the Ache-6-gingerol Complexmentioning
confidence: 99%
“…This highlights the need for a novel efficacious therapy, which is the focus of the manuscript by Rosenberg et al (2023). This study presented significant progress in the development of a safe oxime antidote with favorable pharma- A new outlook on the modulation of cholinergic signal transduction with butyrylcholinesterase (BChE) and its involvement in lipid mechanism is reviewed by Gok et al (2023). In diseases such as Alzheimer, in which elevated BChE and impaired lipid levels are observed, the lipolytic activity of BChE might be involved.…”
Section: Internationalmentioning
confidence: 99%
“…In diseases such as Alzheimer, in which elevated BChE and impaired lipid levels are observed, the lipolytic activity of BChE might be involved. The authors' idea is that lipolytic activity of BChE may contribute to the release of low-level lipid mediators and may play a yet undetermined role in reducing these membrane lipids, which could lead to some sort of compensatory mechanism at high lipid concentrations (Gok et al, 2023). Furthermore, this special issue contains the first behavioral meta-analysis of ACh's pharmacological neuroimaging studies, aimed to determine whether cholinergic modulation impacts the response latency and accuracy measures of attentional performance (Chakraborty et al, 2023).…”
Section: Internationalmentioning
confidence: 99%
“…of non-choline conjugates such as heroin, cocaine, and aspirin. 4,[7][8][9][10][11][12][13][14][15][16] BChE has been referred to as acylcholine acylhydrolase, plasma cholinesterase, pseudocholinesterase, nonspecific cholinesterase or serum cholinesterase in the previous reports. [1][2][3]17,18 However, the name ''butyrylcholinesterase'' was given to the enzyme by the Committee for Human Gene Nomenclature in 1989.…”
Section: Introductionmentioning
confidence: 99%
“…6 AChE is mainly responsible for the hydrolysis of acetylcholine (ACh), while BChE hydrolyzes various choline conjugates including ACh, succinylcholine and butyrylcholine, in addition to a range of non-choline conjugates such as heroin, cocaine, and aspirin. 4,7–16 BChE has been referred to as acylcholine acylhydrolase, plasma cholinesterase, pseudocholinesterase, nonspecific cholinesterase or serum cholinesterase in the previous reports. 1–3,17,18 However, the name “butyrylcholinesterase” was given to the enzyme by the Committee for Human Gene Nomenclature in 1989.…”
Section: Introductionmentioning
confidence: 99%